The African Continental Free Trade Area: A historical moment for development in Africa - Vera Songwe; Jamie MacLeod; Stephen N. Karingi (Journal of African Trade, 2021)
This policy piece surveys the potential of the African Continental Free Trade Area (AfCFTA) as a historical framework for setting Africa on the path toward structural transformation and sustainable development. After evaluating the part that the landmark continental trade integration reform will play in rebuilding better from the pandemic, the paper quantifies the trade-related impacts of the AfCFTA and assesses its contribution beyond trade. It also highlights Economic Commission for Africa's ongoing support to implementation, building on the support the commission has historically provided to regional and continental integration in Africa.
Keywords: 330; AfCFTA; intra-Africa trade policy integration; UNECA